Numerical Pressure Calculation of Unsteady-State Radial Flow on Slighty Compressibility Fluids (Perhitungan Tekanan Secara Numerik untuk Aliran Radial Tidak Stabil pada Fluida Sedikit Kompresibilitas) - Satiawati, Listiana; Dalimunthe, Yusraida Khairani; Sugiarti, Lisa; Abdurrosyid, Sulthon (Konsorsium Cendekiawan Indonesia, 2022)
The numerical pressure calculation has been calculated for the radially unstable fluid flow in a slightly compressible fluid, using fortran soft program and the results are interpreted in the form of a graph of the function of drainage radius and time. This paper also explains how to derive the pressure equation mathematically which fulfills the mass conservation principle, so the fluid continuity equation is obtained using radial / spherical coordinates and the diffusivity equation. By using the solution of the Ei function, the fluid flow in the radial direction of the porous media can be shown. This mathematical derivation is considered important because in unsteady state fluids, the time variable is very important to consider. It can be seen in the resulting graph, the pressure at the outer point has a maximum value then it will decrease as the drainage radius to the well decreases and with increasing time according to the nature of unsteady state flows.